Social Integration of Hearing-Impaired Students by Means of Health-Enhancing and Recreational Activities - Orikhovska, Anna; Andrieieva, Olena; Kashuba, Vitaliy; Lazarieva, Olena; Lytvynenko, Yurii; Kirichenko, Viktoria; Arefyiev, Valerii; Khrypko, Inna (Physical Education Theory and Methodology, 2020)
Purpose: To substantiate and develop a program of health-enhancing and recreational physical activity for the social integration of students with hearing impairments in a higher education institution environment. Materials and Methods. The study involved 65 students with hearing impairments 17–18 years of age (30 males and 35 females). Theoretical analysis and generalization of special scientific and methodological literature, pedagogical experiment, anthropometric measurements of the hearing-impaired, Apanasenko’s method, methods of mathematical statistics were used. Results. The structure and content of the program of health-enhancing and recreational physical activity for students with hearing impairments were scientifically substantiated and developed. The program takes into account the factors, principles, objectives, tasks, methods, organizational and socio-pedagogical conditions for its effective implementation in higher education institutions. The program includes a system for monitoring the results of its implementation and performance criteria. The effectiveness criteria for the health-enhancing and recreational physical activity program were identified as follows: social integration of hearing-impaired students, restoring their psycho-emotional state, and involvement of the young people in regular physical activity. Conclusions. The results of the study confirmed the effectiveness of the developed program of health-enhancing and recreational physical activity in a higher education institution for the social integration of hearing-impaired students.